KARAKTERISASI MINERAL MAGNETIK MENGGUNAKAN METODA SEM DAN XRD UNTUK IDENTIFIKASI PERUBAHAN LINGKUNGAN - Agustine, Eleonora
Abstract : Environmental changes along Cikapundung river system are expected to be identified through analysis of magnetic grains using Scanning Electron Microscopy (SEM) and X-Ray diffraction (XRD). Samples were taken from six sites along the river system in the forms of liquid suspension and sediments. Magnetic grains were then extracted from sediments using a bar magnet. Both extracted grains and sediments were then analyzed using SEM for visual and compound analysis and XRD for mineralogical analysis. Results show that the shape of magnetic grains somewhat changes during transportation processes while compositional changes indicate new sources of magnetic grains presumably from pollution and other anthropogenic sources.